2009
DOI: 10.1093/heapol/czp048
|View full text |Cite
|
Sign up to set email alerts
|

Household surveillance of severe neonatal illness by community health workers in Mirzapur, Bangladesh: coverage and compliance with referral

Abstract: Despite rigorous programmatic effort, reaching neonates within the first 2 days after birth remained a challenge, and parental compliance with referral recommendation was limited, particularly among young neonates. To optimize potential impact, community postnatal surveillance must be coupled with skilled attendance at delivery, and/or a worker skilled in recognition of neonatal illness must be placed in close proximity to the community to allow for rapid case management to avert early deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
4

Year Published

2009
2009
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 26 publications
0
78
4
Order By: Relevance
“…It seems that CHW surveillance improved equity and minimized previously reported bias toward improved care seeking for male children. 16 In spite of the differences in age and sex of enrolled neonates, viral infection isolation rates did not vary by area in 2006 (48% within vs. 41% outside the CHW surveillance area; Table 2). In addition, diagnosis distributions were similar between the 2 areas in 2006.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It seems that CHW surveillance improved equity and minimized previously reported bias toward improved care seeking for male children. 16 In spite of the differences in age and sex of enrolled neonates, viral infection isolation rates did not vary by area in 2006 (48% within vs. 41% outside the CHW surveillance area; Table 2). In addition, diagnosis distributions were similar between the 2 areas in 2006.…”
Section: Discussionmentioning
confidence: 91%
“…It is likely that active surveillance improved recognition of neonatal illness and the decision to seek care, even for neonates in the late neonatal period, which encompasses three-fourths of the neonatal period. 16 Furthermore, similar numbers of male and female infants were evaluated from the CHW surveillance area both in 2006 and after discontinuation of facilitated referrals in 2007. This is in contrast to outside the CHW area, where males were favored with an odds ratio of 2.3 and 2 in 2006 and 2007, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that even when parents are made to recognise the need to seek outside care, decision-making can be problematic. An intervention trial in Bangladesh, in which CHWs conducted intense surveillance of sick newborns, identified two challenges especially for young neonates: reaching neonates within the first two days after birth and 'parental compliance with advice to seek outside care' [46]. Studies in older children conducted in the same setting [47,48], and elsewhere in Uganda [49], have identified challenges to care-seeking as mainly related to cost.…”
Section: Delay 1: Delays In Problem Recognition and Delays In Decidinmentioning
confidence: 99%